Relationships and taxonomy of the genus Diponthus Stål (Orthoptera: Acridoidea: Romaleidae) - Pocco, Martina E.; Lange, Carlos E.; Cigliano, María Marta (Zootaxa, 2023)
Diponthus Stål, one of the most diversified and widely distributed Romaleinae genera, is endemic to southern South America. This colorful grasshopper genus is placed within Romaleini and currently includes 16 valid species from a total of 22 nominal ones, most of them only known from their original descriptions. The aims of this study were to propose a morphology-based phylogenetic hypothesis of relationships among the species of Diponthus, and to conduct a taxonomic revision, including the description of four previously unknown species. Parsimony analysis of 79 morphological characters strongly recovered the monophyly of genus Diponthus, and Gurneyacris as its sister group. Internal clades within Diponthus were supported by external morphology and coloration patterns, while characters from male genitalia were shown to be more useful for species differentiation. Based on the results of the taxonomic review, Diponthus is constituted by 16 valid species, with the following nomenclatural changes proposed: Diponthus nigroconspersus (Stål) is considered a valid name; D. invidus Carl and D. bilineatus Rehn are synonymized under D. virgatus (Gerstaecker); Diponthus clarazianus Pictet & Saussure is synonymized under D. cribratus (Serville); D. paulista Rehn is synonymized under D. porphyreus (Gerstaecker); D. maculiferus (Walker) is synonymized under D. electus (Serville). New names are proposed for four undescribed species from Bolivia (D. colorbellus sp. nov. and D. dilatatus sp. nov.), Argentina (D. paranaensis sp. nov.) and Brazil (D. salvadorii sp. nov.).